Pengembangan Modul Matematika Dengan Strategi Problem Solving Untuk Mengukur Tingkat Kemampuan Berpikir Kreatif Matematis Siswa Di SMP Muhammadiyah Kupang - Asa, Ela Marsela; Zulfikar, Ryan Nizar; Syarief, Nur Hasanah (MEGA: Jurnal Pendidikan Matematika, 2023)
The objectives of this study were to discover the development of mathematics modules with problem-solving strategies to assess students' mathematical creative thinking abilities, and also to describe teachers' and students' reactions to the development of mathematics modules with problem-solving strategies to assess students' mathematical creative thinking abilities. The method used in this study is Research and Development (R&D), which includes stages such as define, design, develop, and disseminate. In this study, data was collected through a validation questionnaire administered by material and media specialists, as well as small group trials and teacher response surveys.Based on the results of stage I validation by the experts, a cumulative average score of 4.08% "very good" with a cumulative score of 4.51% was obtained; in stage 2 validation, the cumulative score was 4.19% "very good" with a cumulative score of 4.68% and testing was appropriate. The result on teacher's responseachieved an average score of 4.04% with the "very good" criteria. In the small group trials, an average score of 3.69% was achieThe objectives of this study were to discover the development of mathematics modules with problem-solving strategies to assess students' mathematical creative thinking abilities, and also to describe teachers' and students' reactions to the development of mathematics modules with problem-solving strategies to assess students' mathematical creative thinking abilities. The method used in this study is Research and Development (R&D), which includes stages such as define, design, develop, and disseminate. In this study, data was collected through a validation questionnaire administered by material and media specialists, as well as small group trials and teacher response surveys.Based on the results of stage I validation by the experts, a cumulative average score of 4.08% "very good" with a cumulative score of 4.51% was obtained; in stage 2 validation, the cumulative score was 4.19% "very good" with a cumulative score of 4.68% and testing was appropriate. The result on teacher's responseachieved an average score of 4.04% with the "very good" criteria. In the small group trials, an average score of 3.69% was achieved with "very good" criteria, while the results of the students' creative thinking test obtained 89.5% with "very good" criteria. Whereas practicality of the module to which the teacher responded received an average score of 4.04% in the "very practical" category and student responses to the module received an average score of 3.69% in the "very practical" category, the module's effectiveness received an average score. -an average of 3.69% in the "very effective" category.The results of the creative thinking test on 10 students VIII B at SMP MuhammadiyahKupang showed that one student had an average test score of 75 in the "quite creative" category, while two students achieved 80. While Seven students are in the "very creative" category between 85-100. it is indicated that the module is acceptable and suitable to be used as teaching material.ved with "very good" criteria, while the results of the students' creative thinking test obtained 89.5% with "very good" criteria. Whereas practicality of the module to which the teacher responded received an average score of 4.04% in the "very practical" category and student responses to the module received an average score of 3.69% in the "very practical" category, the module's effectiveness received an average score. -an average of 3.69% in the "very effective" category.The results of the creative thinking test on 10 students VIII B at SMP MuhammadiyahKupang showed that one student had an average test score of 75 in the "quite creative" category, while two students achieved 80. While Seven students are in the "very creative" category between 85-100. it is indicated that the module is acceptable and suitable to be used as teaching material.